WORLD TRENDS OF THE REDUCTION OF THE MUNICIPAL WASTE LANDFILLS NUMBER ON THE EXAMPLE OF THE USA - Bereziuk Оleg; Kraevskyi, Volodymyr; Bereziuk, Ludmila (Scientific Works of Vinnytsia National Technical University, 2020)
Over the last years the total area of the municipal solid waste landfills and waste dumping grounds has considerably increased, many of these landfills and waste dumping grounds are overloaded, as a result norms of ecological safety are violated and the landfills become the objects of the intensive ecological loading that may lead to the contamination of the environment with harmful substances: heavy metals, microorganisms (colibacilli, streptococci, staphylococci and ascarids), toxic filtrate, landfill gas, etc. The urgent scientific-engineering problem is the determination of the regressive dependences, which describe the dynamics of the number of municipal waste landfills decrease. The aim of the research is the determination of the regressive dependences, which describe the dynamics of the number of the municipal waste landfills decrease. In the process of the research the method of the regressive analysis of the result of the single factor experiments and other pair dependences with the selection of the best type of the function from the sixteen most widely spread variants by the criterion of the maximum value of the correlation factor was used. The regression was performed on the base of the linearized transforms, which enable to reduce the non-linear dependence to the linear one. Determination of the coefficients of the regression equations was carried out, applying the method of least squares, by means of the developed program "RegAnaliz", the program is protected by the certificate of the state registration of the rights to the copyright object. Adequate regression dependences, describing the dynamics of the number of municipal waste landfills decrease are obtained, they can be used for the determination of the necessary number of the dust-carts for the collection and transport of the solid household waste and machines needed for the execution of the technological operations of the compaction on the map of the waste dumping ground. Graphic dependences, describing the dynamics of the number of the municipal waste landfills decrease and allow to illustrate this dynamics and show the sufficient coincidence of the theoretical results with the actual data are constructed.